Assessment of Analytical Specificity in qPCR: SYBR Green and TaqMan Probe Methods for Isonazid-Resistant Mycobacterium tuberculosis - Merdekawati, Fusvita; Suryawan, Muhammad Raihan; Nurhayati, Betty; Rinaldi, Sonny Faisal; Juliastuti, Aditya (Mukhtabar Journal of Medical Laboratory Technology, 2025)
Background & Objective: Mycobacterium tuberculosis, often referred to as M. tuberculosis, is an infectious pathogen that is responsible for causing tuberculosis (TB), a prevalent condition that is a leading cause of death globally. The spread of tuberculosis bacteria that are resistant to certain medicines, such as isoniazid, is currently on the rise. Therefore, molecular testing, such as quantitative polymerase chain reaction (qPCR), is needed to rapidly and reliably identify isoniazid-resistant tuberculosis germs. Method: The purpose of this study was to assess the analytical specificity of TaqMan Probe and SYBR Green qPCR techniques for the detection of isoniazid-resistant tuberculosis. This study was descriptive and quantitative. Analytical specificity was ascertained using MTB DNA with the S315G mutation spiked with E. coli DNA. A paired t-test was used to assess the primary data. Result: The results show that the analytical specificity values based on the significance of the paired t-test for the SYBR Green and TaqMan Probe methods were 0.398 and 0.790, respectively. Conclusion: Based on these results, it can be concluded that the analytical specificity of the TaqMan Probe qPCR method was 1.99 times greater than that of the SYBR Green method.